Law and economics in a nutshell - Harrison, Jeffrey L. 1946- (West Academic Publishing, 2016)
"This guide provides expert coverage of the classic issues, including basic price theory; definitions of efficiency; the Coase Theorem; and the economics of contract law, tort law, criminal law, regulation, antitrust, and intellectual property. The text also discusses less conventional topics such as public choice, what it means to be a rational maximizer of self-interest, the assumptions underlying economic analysis as applied to law, limitations on the application of economic theory to law, the theory of second best, the prisoner's dilemma, the economics of marriage, the economics of inheritance, evolutionary theories of law, the economics of settlement, and the implications of recent research into happiness"--Publisher description
Literaturangaben
Introduction -- Economic tools and concepts -- Normative and behavioral complications in the application of economics to law -- The Coase Theorem and related property issues -- The economics of enforcing promises -- Economics of tort law -- The economics of settlements -- Economic analysis of criminal law -- The economics of antitrust -- The economics of government regulation -- Intellectual property -- The evolution of law -- Tax policy and taxes on intergenerational transfers -- Marriage and divorce -- Public choice
Keywords: Law and economics; Law / Economic aspects / United States; Law / Economic aspects; Recht; United States; USA